Obstetric healthcare experiences and information needs of Dutch women in relation to their vegan diet during pregnancy - Deidre Meulenbroeks; Daisy Jonkers; Hubertina Scheepers; Jessica Gubbels (Preventive Medicine Reports)
Objectives: The prevalence of a vegan (strict plant-based) diet is increasing. Adequate access to nutritional information for pregnant women on a vegan diet is vital, as optimal maternal nutrition is important in order to prevent maternal and fetal complications. This study evaluated the obstetric healthcare experiences and information needs of pregnant women following a vegan diet in the Netherlands. Methods: An online survey examined women’s experiences with obstetric healthcare in relation to their vegan diet during pregnancy. In total, 195 women, all of whom followed a vegan diet during their pregnancy and gave birth between January 2018 and April 2020, completed an online survey about their experiences. Descriptive statistics were used to present the data. Results: In total, 36.5% of participants reported that an obstetric healthcare provider had inquired about their diet in general during the first prenatal consultation, and an additional 43.1% of participants proactively informed their healthcare provider about their diet. Only 19.0% of all participants received specific information about their vegan diet during pregnancy, and 25.2% reported having had extra checks, mostly blood tests, during their pregnancy. Of all participants, 35.9% would have preferred to receive additional information regarding their diet. Conclusions: Our data shows that only a minority of pregnant women following a vegan diet received information and recommendations about their diet from their healthcare providers. It is our recommendation that healthcare providers inquire about pregnant women’s diets, and refer those following a vegan diet to reliable sources of dietary information or to a specialized dietitian.